DAYA INFORMASI AKUNTANSI MEMODERASI PENGARUH POSITIF CORPORATE SOCIAL RESPONSIBILTY TERHADAP COST OF EQUITY CAPITAL - Yuniarta, Gede Adi; Agustini, Yuli (University of Merdeka Malang, 2014)
This research investigated the influence of informativeness of accounting on the relation of Corporate SocialResponsibility disclosure and the cost of equity capital of public companies listed in the Indonesian StockExchange in the period of 2008-2012. Purposive sampling method was used to determine samples and 154observations were obtained. Hypothesis testing was conducted using moderated regression analysis (MRA).This study found that the informativeness of accounting influenced the relation of Corporate Social Responsibilitydisclosure and the cost of equity capital. It weakened the positive impact of corporate social responsibilityon the cost of equity capital. The greater level of Corporate Social Responsibility disclosure accompanied by agood informativeness of accounting by companies, the lower the cost of equity capital was. Corporate SocialResponsibility disclosure with good informativeness accounting would give potential benefits like the growingnumber of investors, reducing estimated risks and asymmetry of information each of which indicated areduction in the cost of equity capital of firms.